Peran Pemerintah Desa dalam Pemberdayaan Produk Lokal Rombeng Razong: Studi Kasus Di Desa Langga Sai, Kecamatan Elar Selatan, Kabupaten Manggarai Timur - Benyamin Yanko Mekor; Frans B. Ricky Humau; Syahrin B. Kamahi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of the Langga Sai Village Government in empowering the local product Rombeng Razong as an effort to enhance the village economy and preserve local cultural identity. Rombeng Razong is a traditional woven craft with high economic and cultural value, yet it has not been fully optimized. The research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the village government, community leaders, local artisans and youth representatives. The findings reveal that the role of the Langga Sai Village Government as a regulator has been realized through the issuance of Village Regulation No. 4 of 2020 on Local Product Protection. However, its roles as a motivator, facilitator, and catalyst have not been effectively implemented due to limited training, technical assistance, and market access. Low community participation and weak institutional structures also hinder the development of Rombeng Razong as an economic commodity. The study concludes that the success of local product empowerment depends not only on formal regulation but also on the effectiveness of village governance, community participation, and cross-sector collaboration. The village government must therefore strengthen its political role as a driver of inclusive development based on local potential.